DIX Domains of Dvl and Axin Are Necessary for Protein Interactions and Their Ability To Regulate β-Catenin Stability - Kishida, Shosei (American Society for Microbiology, 1999)
The N-terminal region of Dvl-1 (a mammalian Dishevelled homolog) shares 37% identity with the C-terminal region of Axin, and this related region is named the DIX domain. The functions of the DIX domains of Dvl-1 and Axin were investigated. By yeast two-hybrid screening, the DIX domain of Dvl-1 was found to interact with Dvl-3, a second mammalian Dishevelled relative. The DIX domains of Dvl-1 and Dvl-3 directly bound one another. Furthermore, Dvl-1 formed a homo-oligomer. Axin also formed a homo-oligomer, and its DIX domain was necessary. The N-terminal region of Dvl-1, including its DIX domain, bound to Axin directly. Dvl-1 inhibited Axin-promoted glycogen synthase kinase 3β-dependent phosphorylation of β-catenin, and the DIX domain of Dvl-1 was required for this inhibitory activity. Expression of Dvl-1 in L cells induced the nuclear accumulation of β-catenin, and deletion of the DIX domain abolished this activity. Although expression of Axin in SW480 cells caused the degradation of β-catenin and reduced the cell growth rate, expression of an Axin mutant that lacks the DIX domain did not affect the level of β-catenin or the growth rate. These results indicate that the DIX domains of Dvl-1 and Axin are important for protein-protein interactions and that they are necessary for the ability of Dvl-1 and Axin to regulate the stability of β-catenin.